Ideas in education - Fink, L. Dee (Universiti Teknologi MARA, Sarawak, 2004)
Many college teachers today want to move past passive learning to active learning, to find better ways of engaging students in the learning process. But many teachers feel a need for help in imagining what to do, in or out of class, that would constitute a meaningful set of active learning activities. The model below offers a way of conceptualizing the learning process in a way that may assist teachers in identifying meaningful forms of active learning.